2022
DOI: 10.1186/s12872-022-02619-4
|View full text |Cite
|
Sign up to set email alerts
|

The association between prothrombin time-international normalized ratio and long-term mortality in patients with coronary artery disease: a large cohort retrospective study with 44,662 patients

Abstract: Background The association between prothrombin time-international normalized ratio (PT-INR) and long-term prognosis among patients with coronary artery disease (CAD) without atrial fibrillation or anticoagulant therapy was still unclear. We analyzed the association of PT-INR levels and long-term mortality in a large cohort of CAD patients without atrial fibrillation or using of anticoagulant drugs. Methods We obtained data from 44,662 patients who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“… 30 As CAD is regularly accompanied by an elevated risk of thrombosis and bleeding, it has been revealed by previous studies that its of great significant relationship between prothrombin time–international normalized ratio (PT-INR) level and CAD processes. 31 , 32 Lower PT-INR levels reflect a higher risk of blood clots, while higher PT-INR levels indicate a higher risk of bleeding. The lower risk of bleeding may help limit the formation of bleeding within the plaque, which further stabilizes the atherosclerotic plaque and reduces the risk of cardiovascular events and death.…”
Section: Discussionmentioning
confidence: 99%
“… 30 As CAD is regularly accompanied by an elevated risk of thrombosis and bleeding, it has been revealed by previous studies that its of great significant relationship between prothrombin time–international normalized ratio (PT-INR) level and CAD processes. 31 , 32 Lower PT-INR levels reflect a higher risk of blood clots, while higher PT-INR levels indicate a higher risk of bleeding. The lower risk of bleeding may help limit the formation of bleeding within the plaque, which further stabilizes the atherosclerotic plaque and reduces the risk of cardiovascular events and death.…”
Section: Discussionmentioning
confidence: 99%
“…Zheng et al ( 22) illustrated that INR is positively correlated with allcause mortality in patients with sepsis, with an adjusted odds ratio (OR) of 1.86 (95% CI: 1.37-2.52) for in-hospital mortality, and an adjusted HR of 1.47 (95% CI: 1.24-1.74) for 1-year mortality. Among patients with coronary artery disease, an increased risk of all-cause mortality has been found in those with high levels of INR (INR > 1.06) during a median follow-up of 5.25 years (23). Ki-Hong et al (24) also reported that prothrombin time-INR prolongation was associated with poor in-hospital survival (adjusted OR = 0.28; 95% CI = 0.11-0.69) in adult out-of-hospital CA with cardiac etiology.…”
Section: Discussionmentioning
confidence: 99%